Hiring Discrimination: An Overview of (Almost) All Correspondence Experiments Since 2005 - Stijn Baert (Institute of Labor Economics (IZA), 2017)
This chapter aims to provide an exhaustive list of all (i.e. 90) correspondence studies on hiring discrimination that were conducted between 2005 and 2016 (and could be found through a systematic search). For all these studies, the direction of the estimated treatment effects is tabulated. In addition, a discussion of the findings by discrimination ground is provided.
Keywords: C93; J71; 330; discrimination; hiring; field experiments; correspondence experiments; correspondence tests